2008
DOI: 10.1158/1078-0432.ccr-07-4722
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Sensitizes Human Colorectal Cancer Xenografts in Nude Mice to γ-Radiation by Targeting Nuclear Factor-κB–Regulated Gene Products

Abstract: Collectively, our results suggest that curcumin potentiates the antitumor effects of radiation therapy in colorectal cancer by suppressing NF-kappaB and NF-kappaB-regulated gene products, leading to inhibition of proliferation and angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
139
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(145 citation statements)
references
References 58 publications
5
139
1
Order By: Relevance
“…This phytochemical also modulates various mechanisms that are associated with radioresistance, including the following: downregulating COX-2, MRP, Bcl-2, and survivin expression; inhibiting PI3K/AKT activation; suppressing growth factor signaling pathways; and inhibiting STAT3 activation (24)(25)(26). The present study demonstrated that Cur enhanced radiosensitivity in the NPC cell line CNE2 at 10 µmol/l by MTT or clonogenic survival test (27), although Cur exhibited higher anti-proliferative effects when used alone at a concentration of 20 or 40 µmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…This phytochemical also modulates various mechanisms that are associated with radioresistance, including the following: downregulating COX-2, MRP, Bcl-2, and survivin expression; inhibiting PI3K/AKT activation; suppressing growth factor signaling pathways; and inhibiting STAT3 activation (24)(25)(26). The present study demonstrated that Cur enhanced radiosensitivity in the NPC cell line CNE2 at 10 µmol/l by MTT or clonogenic survival test (27), although Cur exhibited higher anti-proliferative effects when used alone at a concentration of 20 or 40 µmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…Bimonte et al [175] reported that curcumin inhibits the expression of MMP-9 in orthotopically implanted pancreatic tumors. Curcumin causes a significant reduction of tumor volume, and MMP-9 activity in a xenografted model [176] . Curcumin also reduces the expression of major MMPs via reduced NFκB activity and AP-1 transcription [176] .…”
Section: Curcuminmentioning
confidence: 93%
“…Curcumin causes a significant reduction of tumor volume, and MMP-9 activity in a xenografted model [176] . Curcumin also reduces the expression of major MMPs via reduced NFκB activity and AP-1 transcription [176] . Lin et al [177] reported that curcumin inhibits SK-Hep-1 hepatocellular carcinoma cell invasion via suppression of MMP-9 secretion.…”
Section: Curcuminmentioning
confidence: 93%
“…Classified as type I programed cell death, apoptosis is involved in a number of cancer-related processes, including tumorigenesis, tumor progression and cellular responses to chemotherapy and radiotherapy (4)(5)(6). The well-studied tumor suppressor protein, p53, is key to apoptosis and cancer development.…”
Section: Introductionmentioning
confidence: 99%